Effect of Sexual Knowledge and Attitude, Exposure to Electronic Media Pornography, Peer Group, and Family Intimacy, on Sexual Behaviors among Adolescents in Surakarta - Yeni Wardhani; Didik Tamtomo; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Globalization has tremendous impact on adolescent behaviors, including sexual behavior. Sexual behaviors that exceed socially accepted norms may result in undesireable impact adolescent health. Many factors can affect the sexual behavior of adolescents, both from within and from outside the adolescent self. This study aimed to investigate the effect of sexual knowledge and attitude, exposure to electronic media pornography, peer group, and family intimacy, on sexual behaviors among adolescents.Subjects and Method: This was an analytic observational study using cross-sectional design. The study was conducted at SMA Negeri Kota Surakarta, Central Java, from March to April 2017. A sample of 100 students were selected for this study by multi-stage sampling. The dependent variable was sexual behaviour. The independent variables were sexual knowledge, attitude toward sex, exposure to electronic pornography, peer group, and family intimacy. The data were collected by a set of pre-tested questionnaire. Path analysis was employed for data analysis.Results: Adolescent sexual behavior was affected by sexual knowledge (b=0.16; SE=0.05; p=0.006), attitude toward sex (b=0.18; SE=0.06; p= 0.005), exposure to electronic pornography (b=-0.13; SE=0.05; p=0.026), peer group (b=0.06; SE=0.03; p= 0.042), and family intimacy (b=0.07; SE=0.03; p=0.038). Sexual knowledge was affected by exposure to electronic pornography (b=-0.20; SE=0.09; p=0.037), and peer group (b=0.14; SE=0.05; p=0.005). Attitude toward sex was affected by exposure to electronic pornography (b=-0.21; SE=0.08; p=0.013), sexual knowledge (b=0.14; SE=0.08; p=0.110), and group (b=0.12; SE=0.05; p=0.009). Conclusion: Sexual behavior of adolescents is directly affected by their sexual knowledge, attitude toward sex, exposure to electronic pornography, peer group, and family intimacy.Keywords: sexual behavior, exposure to electronic pornography, PRECEDE PROCEED model, path analysisCorrespondence: Yeni Wardhani. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: ynwardhani@gmail.com. Mobile: +6285244390776.Journal of Health Promotion and Behavior (2017), 2(2): 138-147https://doi.org/10.26911/thejhpb.2017.02.02.04